2011
DOI: 10.1002/dmrr.1156
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia and exercise improve insulin sensitivity (SI2*) in individuals with type 2 diabetes

Abstract: this study demonstrated that (1) hypoxic-induced improvements in glucose tolerance in the 4 h following exposure can be attributed to improvements in peripheral insulin sensitivity (S( I)(2*) and (2) exercise and hypoxia have an additive effect on insulin sensitivity (S(I)(2*) in type 2 diabetic patients. Acute hypoxia may therefore improve short-term glycaemic control in individuals with type 2 diabetes. The application of these findings in the clinic will require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 43 publications
1
105
5
2
Order By: Relevance
“…Other trial 12 demonstrated that IHE glucose tolerance enhancement four hours after exposure can be attributed to improvements in peripheral insulin sensitivity in sedentary males with T2D. Therefore, it may improve short-term glycaemic control [85].Similar to the effects of exercise, increased epinephrine during IHE, which was reported in healthy humans may have contributed to glycogen utilization via increases in cyclic adenosine monophosphate concentrations, potentially leading to post-treatment increased on insulin sensitivity [72].Similarly, it has been described that both IHE and IHT programmes carried out in hypoxic conditions increased glucose transporter GLUT-4 levels [33].Hypoxia and exercise have shown an additive effect on insulin sensitivity [87], suggesting that insulin signalling and insulin-dependent glucose transport, might have been up-regulated following hypoxic exercise [33, 34]. This additive improvement could also be attributed to an increase in the relative intensity of the practised exercise in hypoxia [56].…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Other trial 12 demonstrated that IHE glucose tolerance enhancement four hours after exposure can be attributed to improvements in peripheral insulin sensitivity in sedentary males with T2D. Therefore, it may improve short-term glycaemic control [85].Similar to the effects of exercise, increased epinephrine during IHE, which was reported in healthy humans may have contributed to glycogen utilization via increases in cyclic adenosine monophosphate concentrations, potentially leading to post-treatment increased on insulin sensitivity [72].Similarly, it has been described that both IHE and IHT programmes carried out in hypoxic conditions increased glucose transporter GLUT-4 levels [33].Hypoxia and exercise have shown an additive effect on insulin sensitivity [87], suggesting that insulin signalling and insulin-dependent glucose transport, might have been up-regulated following hypoxic exercise [33, 34]. This additive improvement could also be attributed to an increase in the relative intensity of the practised exercise in hypoxia [56].…”
mentioning
confidence: 78%
“…An increase in body fat is linked with a decline in insulin sensitivity in both obese and elderly individuals, and a recent study showed that acute hypoxic training improved glucose tolerance, and that combined exercise in hypoxic state further ameliorated insulin sensitivity in T2D [87]. Other trial 12 demonstrated that IHE glucose tolerance enhancement four hours after exposure can be attributed to improvements in peripheral insulin sensitivity in sedentary males with T2D.…”
Section: Intermittent Hypoxia and Insulin Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxia is a feature of chronic inflammatory diseases (e.g., cancer) [92], athletic performance and has been used therapeutically to improve the clinical outcomes of certain diseases [93][94][95]. Exposing tissues to stress, such as hypoxia, can lead to cell death that causes the release of DAMPs which are then able to bind to PRRs where they activate ILCs [92].…”
Section: Exercise and The Mobilization Of Ilcsmentioning
confidence: 99%